Antibiotic Susceptibility and Resistance Testing: An Overview - Fiona Smaill (Canadian Journal of Gastroenterology)
The results of in vitro antibiotic susceptibility testing can predict the clinical response to treatment and guide the selection of antibiotics. The minimum inhibitory concentration (MIC) of an organism is the lowest concentration of an antibiotic that will inhibit its growth. Bacteria are classified as sensitive, intermediate or resistant based on breakpoint MIC values that are arbitrarily defined and reflect the achievable levels of the antibiotic, the distribution of MICs for the organism and their correlation with clinical outcome. Broth dilution, agar dilution and gradient diffusion (the ’E test’), where twofold serial dilutions of antibiotic are incorporated into tubes of broth, agar plates or on a paper strip, respectively, are different methods to measure the MIC of an organism. The disk diffusion method defines an organism as sensitive or resistant based on the extent of its growth around an antibiotic-containing disk. MIC values are influenced by several laboratory factors. To ensure reproducible results, the laboratory must closely follow methods developed by the National Committee for Clinical Laboratory Standards, which defines standard growth media, incubation temperature and environment, the inoculum and quality control parameters.